2001
DOI: 10.1093/carcin/22.5.779
|View full text |Cite
|
Sign up to set email alerts
|

The role of the C' terminus of murine p53 in the p53/mdm-2 regulatory loop

Abstract: Mdm-2 plays a central role in the regulation of p53 protein level and activity. Although the interaction of mdm-2 and p53 occurs through the N-terminus of the p53 protein, our present data suggest that the C' terminus plays an important role in the regulation of the p53/mdm-2 loop. Comparative analysis of the murine regularly spliced form of p53 (RSp53) and a physiological C-terminally modified p53 protein, which results from alternative splicing of the p53 mRNA (ASp53), indicated that the two isoforms behave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Mouse double minute 2 homolog (MDM2), also termed E3 ubiquitin-protein ligase (17,18), is an important negative regulator of the p53 tumor suppressor. Mdm2 protein recognizes the N-terminal trans-activation domain of the p53 tumor suppressor and inhibits p53 transcriptional activity (19,20). The p53-MDM2 signaling pathway is known to control cancer invasion and metastasis (21).…”
Section: Overexpression Of Microrna-125a-3p Effectively Inhibits the mentioning
confidence: 99%
“…Mouse double minute 2 homolog (MDM2), also termed E3 ubiquitin-protein ligase (17,18), is an important negative regulator of the p53 tumor suppressor. Mdm2 protein recognizes the N-terminal trans-activation domain of the p53 tumor suppressor and inhibits p53 transcriptional activity (19,20). The p53-MDM2 signaling pathway is known to control cancer invasion and metastasis (21).…”
Section: Overexpression Of Microrna-125a-3p Effectively Inhibits the mentioning
confidence: 99%
“…53 Indeed, p53AS is a less potent transactivator of Bax and p21 promoters, although p53AS has a stronger affinity to p53REs. , 42 Kulesz-Martin et al, 45 Wu et al, 43 Miner and Kulesz-Martin, 49 Wu et al, 47 Almog et al, 53 Wolkowicz et al, 48 Almog et al, 54 Almog et al, 55 and Huang et al…”
Section: P53 Isoforms In Animal Modelsmentioning
confidence: 99%
“…54 The p53AS inhibitory effect on p53-mediated apoptosis is MDM2 dependent, as p53AS is able to induce higher levels of the MDM2 protein than p53. 55 Although p53AS was shown to regulate the expression of several genes including p21, Bax, and Bcl-2, Kulesz-Martin and colleagues reported that p53AS is more effective in transcription repression than p53, highlighting a role of p53 C-terminal domain in this effect. 44 Mouse Δ40p53 isoform (also named ΔNp53 or p44) is expressed in normal tissue through alternative initiation of translation at codon 41.…”
Section: Monographsmentioning
confidence: 99%